O12.3 Multicultural survey – 20 years on: trends in chinese and thai female sex worker demographics and sexual health in sydney. (13th September 2015) - Martin, L; Thng, C; Wand, H; McNulty, A; Foster, R; McGregor, S
Abstract : Social policy, behavioural change, psychosocial or psychosexual issues related to sexual health. Background: Studies from Sydney Sexual Health Centre (SSHC) in 1993 and 2003 found changes in demographics and safe sex practices of culturally and linguistically diverse (CALD) sex workers attending SSHC over time. We aimed to establish if there are further changes in 2014. Methods: A cross sectional survey of CALD sex workers attending SSHC and parlours visited on outreach, was conducted from June 2014 to February 2015. The survey included questions from surveys conducted in 1993 and 2003, so trends could be identified. All studies used an anonymous questionnaire translated into Thai and Chinese. Results were analysed by pair-wise comparisons. Results: In 2014, 338 participants were included in the analysis, compared to 65 and 91 participants in 2003 and 1993 respectively. Comparing 2014 to 2003, there was a 91% (p < 0.001) increase in workers with <10 years of education, matched by a similar trend in poor levels of spoken English. Two thirds (66%) of workers were on student visas in 2014 compared to 26% in 2003. Workers who have been on contract decreased from 27% in 1993 to 9% in 2003 (p = 0.0001) and 8% in 2014 (p = 0.67). Consistent condom use for vaginal sex increased by 49% (p < 0.001) in 2014 compared to 1993. However there was a 9% (p = 0.038) decrease between 2014 and 2003, with similar trends in consistent condom use for oral sex. The provision of free condoms has decreased from 63% in 1993 to 22% (P < 0.001) in 2014. Conclusion: From 2003 to 2014, there has been a decrease in the level of education and English proficiency among CALD sex workers, which may impact on the ability to negotiate sex work safely. There is increased consistent condom use in 2014 compared to 1993, but there has been a downward trend in the last 10 years. Education and access to health services remains crucial for CALD sex workers. Disclosure of interest statement: No conflict of interest.